PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN - Nadia Ulfa Rahayu (2022)
This research was conducted to test and prove the influence of corporate social responsibility (CSR) and good corporate governance (GCG) on company value with company size as a moderation variable. This research focuses on energy and raw material sector companies in 2019-2021. The samples in the research were 57 data samples selected by the purposive sampling method. This research belongs to the quantitative-secondary type. Random Effect Model (REM) with panel data regression was used in this study using STATA13 M P (64-bit). The degree of significance used is 5%. The results of the study found that: 1) corporate social responsibility (CSR) has a significant effect on company value; 2) the audit committee has no significant effect on the value of the company; 4) the size of the company moderates the influence of corporate social responsibility on the value of the company; 5) the size of the company does not moderate the influence of the audit committee on the value of the company; 6) The size of the company does not affect the independent board of commissioners on the value of the company. Keywords: Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Audit Committee, Independent Board of Commissioners, and Company Size.